Las obligaciones tributarias y su incidencia en el riesgo tributario de la Empresa Estratex, periodo 2018. - Estrada Cabrera, Erika Lizbeth (2022)
This research work is focused on "Tax obligations and their incidence on the tax risk of the company ESTRATEX, period 2018" its main objective is to determine the degree of incidence of non-compliance with tax obligations on the fiscal tax risk. The company ESTRATEX has complied with its formal duties under the precepts of tax legality to the SRI (Internal Tax Service in English) when carrying out this investigation some irregularities were detected in the fulfillment of its tax obligations, among the most common ones we have the variation generated by the difference in declared values and the values reviewed, thus generating tax risk for the company; It was also possible to detect that there was no adequate calculation of the tax credit in favor of the company in 3 months of the year under study, thus causing risk for the entity. For this research work it was necessary to carry out a deductive logical investigation, of a documentary and field type, since the information presented to the Tax Administration was compiled, supported and compared with the documents provided by the company, it was also non-experimental since it does no alteration of documents. With the documentation provided by the entity, it allowed to issue the corresponding conclusions, these conclusions will help to reduce the fiscal tax risk.